Terrestrial Invasive Plant Survey in Eau Claire County, Wisconsin - Hon, David; Moris, Matthew; Kelly, Jeanette (My University, 2012)
Terrestrial invasive plant species are non-native plants that spread outside their natural range and take advantage of degraded or disturbed environments. They are harmful to local ecosystems as some invasive species may outcompete native species (Wisconsin Department of Natural Resources, 2010). Beaver Creek Reserve's Citizen Science Center conducted a baseline survey in the Summer of 2011 which aimed to identify the exact location, abundance and ecotypes of invasive species.
Color poster with text, images, maps, charts, and tables.
Keywords: Invasive plants--Eau Claire County--Wisconsin--Identification; Eau Claire County (Wis.)--Environmental conditions; Posters